2009
DOI: 10.1677/erc-08-0266
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to chemotherapy and hormone therapy in endometrial cancer

Abstract: Endometrial cancer is the most common gynecological malignancy in developed countries and represents the eighth leading cause of cancer related death in women. The growing incidence of endometrial cancer leads scientists and oncologists to identify effective preventive measures and also molecular markers for diagnosis and prognosis. Chemotherapy and hormone therapy is the mainstay treatment option for advanced and recurrent endometrial cancer and response to therapy is one of the most important factor which fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 149 publications
0
87
0
1
Order By: Relevance
“…Further studies are needed to elucidate the mechanisms and effects of Pak4 on cell proliferation in short-term and longterm cultures. The efficacy of anticancer therapies depends not only on the cellular damage they cause but also on the cell's ability to respond to these damages by inducing the apoptotic response [42]. Although we observed that Pak4 had no significant effect on EC cell apoptosis under regular culture conditions, Pak4 was found to protect HeLa and NIH3T3 cells from apoptosis induced by TNF-α and UV irradiation [43,44].…”
Section: Discussionmentioning
confidence: 64%
“…Further studies are needed to elucidate the mechanisms and effects of Pak4 on cell proliferation in short-term and longterm cultures. The efficacy of anticancer therapies depends not only on the cellular damage they cause but also on the cell's ability to respond to these damages by inducing the apoptotic response [42]. Although we observed that Pak4 had no significant effect on EC cell apoptosis under regular culture conditions, Pak4 was found to protect HeLa and NIH3T3 cells from apoptosis induced by TNF-α and UV irradiation [43,44].…”
Section: Discussionmentioning
confidence: 64%
“…Chemotherapy and hormonal therapy play important roles in first-line management of endometrial tumors; however, the majority of patients with advanced endometrial cancer relapse and face a dismal prognosis (20). Similarly, advanced and metastatic sarcoma is rarely curable, as standard chemotherapy has a low response rate, and consequently patient prognosis remains poor (21).…”
Section: Introductionmentioning
confidence: 99%
“…Endometrial cancer is the most common gynecological malignancy worldwide and represents the eighth leading cause of cancer-related deaths in women (1)(2)(3). Most endometrial adenocarcinomas are characterized by positive nuclear estrogen receptor (ER) expression and responsiveness to hormone stimulation.…”
Section: Introductionmentioning
confidence: 99%